Asian Conference at Wrocław University of Economics - Drelich-Skulska, Bogusława; Jankowiak, Anna H. (Economics of the 21st Century, 2014)
On 16-17 November 2014 at Wrocław University of Economics there was held an international scientific conference Redefinition of the Role of Asia-Pacific Region in the Global Economy. Partnership or Leadership? The conference in the series − Asia-Pacific Region took place for the seventh time, and like every year, attracted great interest of the participants and audience
Ekonomia XXI Wieku = Economics of the 21st Century, 2014, Nr 4 (4), s. 144-145